Pengembangan Sistem Kelistrikan Kapal untuk Mendukung Operasional Sea and Coast Guard Indonesia - Edy Prasetyo Hidayat; Daisy Dwijati Kumala Ratna Antariksih; Imam Sutrisno; Ardiansyah; Didik Dwi Suharso (Bulletin of Community Engagement, 2024)
Sea and Coast Guard (SCG) Indonesia has an important role in maintaining Indonesian maritime security and safety. SCG operations require a reliable and efficient electrical system to support various missions, such as patrol, search and rescue, maritime law enforcement, and disaster management. This research aims to develop a ship electrical system that meets the operational needs of SCG Indonesia. This research begins with an analysis of the power requirements and load characteristics of SCG Indonesia. Based on the analysis results, the ship's electrical system was designed by considering several factors, such as energy efficiency, reliability and redundancy. This research also develops operational and maintenance strategies for ship electrical systems to ensure optimal performance. The research results show that the ship electrical system developed is able to meet SCG Indonesia's operational needs with high energy efficiency and good reliability. What are the power requirements and load characteristics of SCG Indonesia? What are the factors that need to be considered in designing a ship's electrical system for SCG Indonesia? What is the optimal operation and maintenance strategy for the SCG Indonesia ship electrical system? Analysis of the power requirements and load characteristics of SCG Indonesia shows that the ship's electrical system must be able to provide sufficient power for SCG Indonesia's various missions. A ship's electrical system is designed with energy efficiency, reliability and redundancy in mind. An optimal operation and maintenance strategy for the SCG Indonesia ship electrical system was developed.